Analisis Visual Kostum dan Atribut Sekhmet dalam Komik Marvel - Syaima Antar Morsi; Yully Ambarsih Ekawardhani (Universitas Komputer Indonesia, 2021)
The purpose of this study is to analyze the costume and attributes of Sekhmet's character in one of marvel's comic books titled